2023
DOI: 10.3389/fpls.2023.1269212
|View full text |Cite|
|
Sign up to set email alerts
|

Characterization of Triticum turgidum sspp. durum, turanicum, and polonicum grown in Central Italy in relation to technological and nutritional aspects

Samuela Palombieri,
Marco Bonarrigo,
Alessandro Cammerata
et al.

Abstract: IntroductionWheat is a staple food, with the two most common species being Triticum aestivum and Triticum turgidum ssp. durum. Moreover, the latter, T. turgidum, includes other tetraploid subspecies, among which the sspp. turanicum (Khorasan wheat) and polonicum (Polish wheat), whose importance has increased in the last decades, representing alternative crops for marginal areas, in addition to being a source of genetic diversity.MethodsIn this work, different accessions of these three subspecies of T. turgidum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Several studies demonstrated that some of these accessions have a higher content of phenols [ 8 , 9 , 10 ], a higher concentration of minerals [ 11 ], and increased prebiotic carbohydrates [ 12 ] compared to elite varieties. Other studies supposed that their superior beneficial effects were not due to their characteristic of being “old” but that they are more related to genotype and growth conditions [ 13 , 14 , 15 , 16 , 17 ]. To prove the beneficial-promoting attributes of ancient varieties, further investigations are required, with standard analysis methods on multiple genotypes of old and modern wheat grown in replicated multi-site field trials [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies demonstrated that some of these accessions have a higher content of phenols [ 8 , 9 , 10 ], a higher concentration of minerals [ 11 ], and increased prebiotic carbohydrates [ 12 ] compared to elite varieties. Other studies supposed that their superior beneficial effects were not due to their characteristic of being “old” but that they are more related to genotype and growth conditions [ 13 , 14 , 15 , 16 , 17 ]. To prove the beneficial-promoting attributes of ancient varieties, further investigations are required, with standard analysis methods on multiple genotypes of old and modern wheat grown in replicated multi-site field trials [ 18 ].…”
Section: Introductionmentioning
confidence: 99%